Urgensi komunikasi interpersonal pustakawan dalam melayani pemustaka - Bella, Elsa Listia; Masruri, Anis; Bagas Aldi Pratama; Hati Murdani (Nur Science Institute, 2024)
Introduction: Librarians will encounter various personalities and characters of librarians when helping them. For librarians, it is important to improve interpersonal communication skills to deal with this. The main goal is to provide the best service to users. In this case, it is very important for librarians to have interpersonal communication skills in serving users. Research mMethod: This research uses the library research method, then collects data using secondary sources such as books, journal articles, documents and other means such as websites. Data Analysis: there are three stages in analyzing this research data, namely, collecting data, selecting data and then verifying the data. Results and Discussion: There are several attitudes to have good interpersonal skills, namely, empathy, supportiveness, positiveness, equality, confidence, Immediacy, interaction management. Then there are influencing factors, namely source, encoding, message, channel, receiver, decoding, response, interference, and context in communication. Apart from that, there are several other influencing factors such as cultural background, education, and so on. Furthermore, the urgency of interpersonal communication for librarians occurs because it is considered the most successful in changing the attitudes, beliefs, views and behavior of communicants. Conclusion and Recommendations: Strong communication skills developed by librarians will enable recognizing and understanding the needs and characteristics of librarians. So it is important for librarians to have interpersonal communication skills, listening ability; skills in providing services; and skills in conveying information.